Nutrition – between healthy eating and sustainable agri-food systems (Research, Society and Development, 2022)
The history of Nutrition in Brazil was based on the biological and clinical approach to food, called nutritionism, characterized by the emphasis on the overestimation of the role that some nutrients would play on health. The social and scientific transformations recurring in the transition to the 21st century, when the social and natural worlds became more influenced by the reflexivity of human knowledge, assuming a strategic role the notions of ecological, climatic and global crisis, risks and sustainability, brought new approaches to the field of nutrition. As a result, questions about nutritional reductionism emerged, seeking to establish systemic connections between the notion of nutrition and the multiple dimensions of sustainability. Thus, we aim here to present and discuss the emerging connections between the notions of nutrition and sustainability, mainly referring to the notion of sustainable agrifood systems. To this end, we carried out an extensive survey and literature review, using document and content analysis. The connective axis between nutrition - healthy eating - sustainability points out that conventional agri-food systems have caused environmental degradation, health problems and inequity in access to food. Hence the need for sustainable agrifood systems for effective healthy eating, bringing relevant impacts to society and planetary health, especially in a post-pandemic context of Covid-19. With regard to the current context of Brazilian Nutrition Science, we consider that there are signs of progress in the sense of recognizing the importance of considering sustainability in agrifood systems for the recommendations of healthy eating. However, many challenges remain to be faced and overcome.